Brucine Entrapped Titanium Oxide Nanoparticle for Anticancer Treatment: An In Vitro Study - Rashed M. Almuqbil (Advances in Pharmacological and Pharmaceutical Sciences)
Backgroundand Objective. The public’s health has been seriously threatened by cervical cancer during recent times. In terms of newly diagnosed cases worldwide, it ranks as the ninth most prevalent malignancy. Multiple investigations have proven that nanoparticles can effectively combat cancer due to their small dimensions and extensive surface area. In the meantime, bioactive compounds which are biocompatible are being loaded onto nanoparticles to promote cancer therapy. The current study investigates the anticancerous potential of Brucine-entrapped titanium oxide nanoparticles (TiO2 NPs) in cervical cancer cell line (HeLa). Materials and Methods. The physiochemical, structural, and morphological aspects of Brucine-entrapped TiO2 NPs were evaluated by UV-visible spectrophotometer, Fourier transform-infrared spectroscopy (FT-IR), dynamic light scattering (DLS), scanning electron microscopy (SEM), and energy dispersive X-ray (EDAX). The cytotoxic effect against the HeLa cell line was assessed using a tetrazolium-based colorimetric assay (MTT), a trypan blue exclusion (TBE) assay, phase contrast microscopic analysis, and a fluorescence assay including ROS and DAPI staining. Furthermore, estimation of antioxidant markers includes catalase (CAT), glutathione (GSH), and superoxide dismutase (SOD). Results. The UV spectrum at 266 nm revealed the formation of TiO NPs. The FT-IR peaks confirmed the effective entrapment of brucine with TiO2 NPs. The average size (100.0 nm) of Brucine-entrapped TiO2 NPs was revealed in DLS analysis. The micrograph of the SEM revealed the formation of ellipsoidal to tetragonal-shaped NPs. The Ti, O, and C signals were observed in EDAX. In MTT assay, Brucine-entrapped TiO2 NPs showed inhibition of cell proliferation in a dose-wise manner and IC50 was noticed at the concentration of 30 µg/mL. The percentage of viable cells gradually reduced in the trypan blue exclusion assay. The phase contrast microscopic analysis of Brucine-entrapped TiO2 NP-treated cells showed cell shrinkage, cell wall deterioration, and cell blebbing. The intracellular ROS level was increased in a dose-wise manner when compared to control cells in ROS staining. The condensed nuclei and apoptotic cells were increased in treated cells, as noted in DAPI staining. In treated cells, the antioxidant markers such as CAT, GSH, and SOD levels were substantially lower compared to the control cells. Conclusion. The synthesized Brucine entrapped TiO2 NPs exhibited remarkable anticancer activity against the HeLa cell line.